Rethinking The Concept Of Entrepreneurial Emergence: A Perspective Of The Individual As The Focus - Akpor-Robaro, M.O.M. (Advances in Social Sciences Research Journal, 2018)
The paper explores the concept of entrepreneurial emergence in the context of pre-organization event and located the core focus of entrepreneurial emergence in the individual thought process. It takes a radical departure from existing views to develop a new meaning of the concept and refers to this as the relevant interpretation. It identifies that entrepreneurial emergence is not the same as the coming to being of an enterprise but the budding of entrepreneurial mind in an individual. The coming to being ofan enterprise is essentially an organizational emergence separate from entrepreneurial emergence. Entrepreneurial orientation and intention are the core components of entrepreneurial emergence. Fundamentally, the paper presents a platform for identifying why and how people become entrepreneurs and uses the concept to capture the initialization stage of becoming an entrepreneur. The perspective presented in the paper represents the birth of a new thought about the concept of entrepreneurial emergence which is expected to stimulate deeper examination of the contending views and theories.